Strength and Deformation Characteristics of Reconstituted Sand under Different Stress Paths in True Triaxial Tests - Hasbullah Nawir; Bagus Eko Prasetyo; Andhika Sahadewa (Journal of Engineering and Technological Sciences, 2020)
To improve the geotechnical stress"“strain analysis, the stress"“strain behavior of geomaterial under general three-dimensional stress conditions prevailing in the field need to be captured. The true triaxial apparatus is an enhanced version of the conventional triaxial apparatus, which allows to simulate stresses by applying loadings independently in 3 orthogonal directions. This study evaluated the strength and deformation behavior of Bangka sand under true triaxial test conditions. The test specimens were prepared by means of the multi-sieve sand pluviation method. Various true triaxial test stress paths were applied under axial compression, lateral extension, axial extension, and lateral compression with the objective of understanding and developing the empirical correlation of coarse-grained soil strength parameters in axial compression stress paths related to other stress paths. The test results showed that an increase in the value of b, the parameter used to quantify the relative magnitude of the intermediate principal stress to the other principal stresses, resulted in an increase of the internal friction angle and a decrease of the peak stress ratio. In addition it was observed that the Lade-Duncan failure criterion fitted the results of this study better than other failure criteria, namely the extended von Mises, Mohr-Coulomb, and Matsuoka-Nakai failure criteria.